Arthur meets the President - Brown, Marc Tolon (Boston : Little, Brown and Company, 1991)
Arthur$1 (Bs essay wins a contest and he has to read it to the President in a special ceremony at the White House.s
Keywords: Presidents -- Fiction; Aardvark -- Fiction; Animals -- Fiction; Contests -- Fiction; Public speaking -- Fiction